Writing on the wall: writing education and resistance to isolationism - Martins, David S., editor; Schreiber, Brooke R., editor; You, Xiaoye, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2023)
The first concerted effort of writing studies scholars to interrogate isolationism in the United States, Writing on the Wall reveals how writing teachers-often working directly with students who are immigrants, undocumented, first-generation, international, and students of color-embody ideas that counter isolationism.--Provided by publisher.
Writing education across borders, an anti-isolationist project / David S. Martins -- On the semantic borders of white nationalism / Keith Gilyard -- Strangers in a strange land: "the foreign student" at US universities after World War II / Amy J. Wan -- "To supplant ignorance requires instruction": literacy as transnational racial project in the colonial Philippines / Florianne Jimenez Perzan -- Scaling cosmopolitanism in the age of precarity / Tony Scott -- Writing to mend literate fragmentation / Rebecca Lorimer Leonard -- Multilingualism beyond walls: undocumented young adults subverting writing education / Sara P. Alvarez -- Public pedagogy and multimodal learning on the US-Mexico border / Layli Maria Miron -- Combatting isolationism through COIL virtual exchange: programmatic and pedagogical perspectives / Olga Aksakalova and Tuli Chatterji -- Fostering cosmopolitanism: international educational partnerships in a professional communication course / Joleen Hanson -- Smoothing the path: Chinese-American joint degree programs as resistance to nationalism / Brooke R. Schreiber and Brody Bluemel.
Keywords: English language -- Rhetoric -- Study and teaching (Higher) -- Social aspects; English language -- Rhetoric -- Study and teaching (Higher) -- Political aspects; Isolationism -- United States; Multicultural education; Transnationalism -- Social aspects